ASUHAN KEBIDANAN PADA NY. S UMUR 33 TAHUN USIA KEHAMILAN 33 MINGGU 1 HARI DENGAN KEHAMILAN HEMOROID DI RUMAH SAKIT ELISABETH MEDAN TAHUN 2018 - Bernadetta Ambarita; Winda Mintauli Sinurat (STIKes Santa Elisabeth Medan, 2018)
Hemorhoids are one of the most common gastrointestinal disorders found in everyday practice and are often the main differential diagnoses for almost all anorectal complaints. (murdani Abdullah 2014). Hemorhoid in pregnant women is common and is a physiological condition that accompanies pregnancy. Pregnancy will increase the incidence of hemorhoid, where more than 50% of pregnant women encountered this case. The risk will increase by 20-30% after the second pregnancy or more. Surgical treatment of hemorrhoidectomy is an option that must be taken by pregnant women if treatment conservatively fails. (Leliana Carolina; 2014).Goals : Able to perform Midwifery Care on Mrs.S Age 33 Years old Pregnancy age 33 Weeks 1 Day With Hemoroid Pregnancy At Elisabeth Hospital Medan in 2018 by using the varney midwifery management approach and solve the problem if there is a gap between practice and theory in pregnant women.Methods: Based on the case study on Mrs.S, the method used for data collection was primary data consisting of physical inspection appears there was swelling on the nus, the pain.Result: Based on case of Mrs.S with hemorhoids pregnancy done handling for 3 days in Elisabeth Hospital Medan. After handling the pain and giving therapy.Conclution : Midwifery care on Mrs.S with Hemoroid Pregnancy in its execution there is no gap between theory and practice in the field.